Integrated Geo Hazard Management System in Cloud Computing Technology - Hanifah M.I.M.; Omar R.C.; Khalid N.H.N.; Ismail A.; Mustapha I.S.; Baharuddin I.N.Z.; Roslan R.; Zalam W.M.Z. (Institute of Physics Publishing, 2023)
Cloud computing; Decision making; Engineering research; Environmental management; Environmental technology; Hazards; Information management; Losses; Safety engineering; Technology; Cloud computing technologies; Computer technology; Database management; Development activity; Environmental health; Flexible measuring systems; Geo hazards; Managing; Distributed computer systems